hey guys can anyone help me find the first and second derivatives of these four problems.
f(x)= (-6x)/(x-2)^2
f(x)=(x-1)(x+2)/(x+1)^2
f(x)=(x+2)^4(4-3x)
f(x)=x^3-6x^2+3x+10
I'll do this. I'll tell you what rule you have to apply, but it's up to YOU to attempt the question.
1) Quotient rule
2) Quotient and product rule
3) Power and product and chain rule
4) Power rule .
You problems are far greater than anything i can help you with if you don't know what these terminologies mean or how to apply them.